A new algorithm for eco-friendly path guidance focused on electric vehicles. (15th October 2021) - Ku, Donggyun; Choi, Minje; Yoo, Nakyoung; Shin, Seungheon; Lee, Seungjae
Abstract: The automobile industry is showing increasing interest in eco-friendly electric vehicles (EVs) with the aim of replacing vehicles that rely on traditional fossil fuels for energy. This study investigates the routing of an EV with maximum efficiency relative to the terrain. As EVs have poor climbing ability due to limitations associated with battery efficiency, this study determines the optimal route using 3D spatial information data and the slope of each link in the route. In the transportation field, the Bureau of Public Roads function classifies the shortest paths and optimizes paths. By adding slope-related variables, a new functional expression that includes weighting as a result of slope-related speed reduction is constructed, and a new functional expression system and network are built. As a result of assigning a route to optimize battery efficiency, the energy efficiency was improved by 7.84 km/kWh at an average speed of 70 km/h. The effectiveness was verified by comparing the total travel time and energy efficiency differences between the two methods. The proposed approach enables efficient transport and ultimately achieves the goal of green transportation with maximum energy efficiency. Highlights: Routing electric vehicles with maximum efficiency depending on the terrain. Electric vehicles have poor climbing ability due to limitations associated with battery efficiency. Optimal route using 3D spatial information data and the slope that was calculated by digital elevation model of each link in the route. More efficient operation is possible if the route selected based on battery efficiency is used. The effect of activating eco-friendly vehicles is reducing carbon emissions.